2017
DOI: 10.1016/j.neurobiolaging.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between age and perceptual similarity in olfactory discrimination learning in F344 rats: relationships with spatial learning

Abstract: Emerging evidence suggests that aging is associated with a reduced ability to distinguish perceptually similar stimuli in one’s environment. As the ability to accurately perceive and encode sensory information is foundational for explicit memory, understanding the neurobiological underpinnings of discrimination impairments that emerge with advancing age could help elucidate the mechanisms of mnemonic decline. To this end, there is a need for preclinical approaches that robustly and reliably model age-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…Given that age‐related discrimination deficits can be predictive of memory loss, both in elderly humans (Stark et al, ) and animal models (La Sarge et al, 2007; Yoder et al, preliminary acceptance Yoder et al, ), rats were cross‐characterized for spatial learning and memory abilities using a Morris water maze task (Bizon et al, ; Gallagher et al, ; Johnson et al, ). Cumulative integrated path length (CIPL) values across the 4 blocks of training trials are shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that age‐related discrimination deficits can be predictive of memory loss, both in elderly humans (Stark et al, ) and animal models (La Sarge et al, 2007; Yoder et al, preliminary acceptance Yoder et al, ), rats were cross‐characterized for spatial learning and memory abilities using a Morris water maze task (Bizon et al, ; Gallagher et al, ; Johnson et al, ). Cumulative integrated path length (CIPL) values across the 4 blocks of training trials are shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are consistent with our findings that aged F344 × BN rats in the present cohort did not show spatial learning or memory impairments relative to their young counterparts, even though these aged rats showed consistent, correlated deficits on similar object discriminations across Experiments 1 and 2. Interestingly, in F344 rats that show more robust water maze deficits with advancing age, as compared to hybrid strains (LaSarge & Nicolle, ), sensory discrimination abilities are highly predictive of spatial memory impairments (LaSarge et al, ; Yoder et al, ). Together, these data suggest application of the rodent target–lure discrimination task could permit detection of the earliest signs of age‐related neurobiological change across cortical–hippocampal circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Because the β oscillations that we found were primarily time locked to head entry into the food cup and well before reward delivery, the data suggest that this is an event of particular relevance to aged rats. Importantly, aged rats show intact thresholds for olfactory cue detection ( Yoder et al, 2017 ). It is possible that aged rats may have formed an association between the residual vanilla scent of the food cup area and upcoming rewards, although not required for accurate performance in any of the tasks administered here.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because attrition resulted in a relatively small number of rats cross-characterized on some tasks, aged rats were divided (based on a median split) to create subgroups corresponding to the upper and lower halves of the distribution on each behavioral measure. Performance on the intertemporal choice task was then compared between these subgroups and young rats using a two-factor ANOVA (subgroup × delay) as in previous work from our laboratories and others (e.g., Beas et al, 2013; Bizon et al, 2009; Leal et al, 2017; Lee et al, 2005; Yoder et al, 2017). …”
Section: 0 Methodsmentioning
confidence: 99%